Papillary thyroid microcarcinoma: the significance of high risk features. Issue 1 (December 2017) - Bradley, Nori; Wiseman, Sam
Abstract Background Papillary carcinomas that measure 1.0cm or less are diagnosed as papillary thyroid microcarcinomas (PTMs). The clinical significance and recommendations for management of these PTMs is still evolving. The objective of the study was to compare the characteristics of small (<5mm) to large (≥ 5mm) papillary thyroid microcarcinomas. Methods Amongst 1459 sequential patients undergoing thyroid surgery at a single center, 132 (9%) cases were diagnosed with PTM. We performed a retrospective analysis of these cases using Fisher's Exact Test. The statistical significance was set atp < 0.05 a priori. Results A relationship between large PTM and high risk features was observed only for extra-thyroidal cancer extension (ETE). Six of 57 large PTM (11%) but none of the 75 small PTM had ETE (p < 0.01). Lymph node metastases were associated with both small PTM (5/9 cases) and large PTM (4/9 cases). A distant metastases was diagnosed in association with a small PTM. Conclusions For PTM, neither small cancer size, nor the absence of high-risk features, excluded the possibility of synchronous lymph node metastases.